Tobacco-related lung cancer burden in the Western Pacific Region from 1990 to 2021: An age-period-cohort analysis from the Global Burden of Disease Study - Rui Wang+; Zhiqiang Zhang+; Xiaoxi Shan+; Jiayang Dong; Xinyue Yang; Jing zhang; Jie Cao (Tobacco Induced Diseases)
Introduction Lung cancer is a significant health issue in the Western Pacific region, where tobacco use is highly prevalent. This study examines the trends in tobacco-related lung cancer burden from 1990 to 2021, offering insights into the evolution of this critical public health challenge.